QUALITY OF EDUCATIONAL SERVICE IN UKRAINIAN HIGHER EDUCATION INSTITUTIONS: CHALLENGE-RESULT PARADIGM - Kukharska , Liliia (Collection of scientific papers «ΛΌГOΣ», 2022)
The final result of the activity of higher education institutions are educational services as a process of meeting intangible needs of consumers for knowledge and goods in the form of textbooks, manuals, monographs, methodological developments, etc. The essence, main consumers and key characteristics of educational services are established. The basic definitions of the concept "quality of education" were studied and it was proposed to replace it with three independent and non-identical concepts: "quality of educational service", "the level of education or received knowledge in the process of learning" and "efficiency of building and functioning of educational system", reflecting different sides of higher education institutions’ activities. The views of scientists on the essence of the concept "quality of educational services" or "quality of higher education service" are characterized and its own interpretation is offered.